A comparison between the glidescope and the mccoy laryngoscope in manikin model with manual in-line stabilization technique - Mohd Rosdie, Mat Jahaya (2011)
Intubation of the trachea in patients with cervical spine injury is a challenging situation. Such acute trauma that requires direct laryngoscopy is accomplished with a standard manoeuvre of manual in-line stabilization technique. Unfortunately this technique creates unnecessary cause of difficult airway. Ideally intubation should be easy, fast and cause minimal cervical spine movement in cases of head and neck injury. There is a hope of indirect laryngoscopy with the GlideScope to achieve these goals. We did a study comparing the GlideScope with the McCoy laryngoscopes in manual in line stabilization (MILS) technique in manikins. This prospective and cross over study involved a total number of 4 7 participants who were anaesthetic resident. Following a brief didactic instruction on the GlideScope and the McCoy each participant took tum performing laryngoscopy and intubation with each device. They were evaluated for each device on their success rate of intubation, mean intubation time, glottic score improvement and their preferences oflaryngoscopy. We found that the success rate of intubation was 91.5% among the McCoy laryngoscope and 87.2% among the GlideScope users. Statistically these figures were not significant with p value of0.727. The McCoy laryngoscope intubations were faster than the GlideScope. The mean times of intubation were 24.4 second ±SD 15.97 and 35.3 second ±SD 17.56, respectively. The p value was significant (p value <0.001). The modified Cormack Lehane Score (CLS) in class I and II were greater with the GlideScope (72.3%) than the McCoy (46.8%). The CLS at moderate class of glottis IIIb to lila was improved for 60% and class lila to II for 73%. Among the participants, their preference of laryngoscope was almost the same where 53.2% had chosen the McCoy while another 46.8% of them favoured the GlideScope. In this study using manikins, mean intubation time was significantly faster in the McCoy group. On the other hand, the glottic score and dental trauma complications were found to be improved significantly in the GlideScope users. There was no significant difference in the success rate and easiness of intubation. Both laryngoscopes were being equally preferred among the participants. Overall, the GlideScope performance has comparable efficacy with the McCoy in this difficult airway, except it conferred greater improvement in the glottis score view. Unfortunately this did not facilitate intubation faster and easier than the McCoy. The GlideScope may be a good alternative for managing the difficult airway but clinical trials evaluating its use on patients with an actual difficult airway are needed.